2023
DOI: 10.18485/meattech.2023.64.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and Extrinsic Factors Impacting Fresh Goat Meat Quality: An Overview

Mohammed Gagaoua,
Laura Alessandroni,
Annada Das
et al.

Abstract: Goat meat, known also as chevon or caprine meat, is an important source of protein and essential nutrients in many regions worldwide. To ensure high-quality goat meat production, it is crucial to understand the intrinsic and extrinsic factors that influence its sensory, technological and nutritional properties. This review aims to provide an overview of the factors affecting goat meat quality throughout the production and processing chain. The importance of different factors influencing goat meat quality were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 121 publications
(181 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that feeding goats with a grain diet containing threefold C18:1 compared to an alfalfa hay diet increased C18:1 in both IMF (i.e., marbling) and subcutaneous fat. Thus, when East African goats were supplemented with a grain diet (27% sunflower seed cake + 70% maize bran), the proportions of C18:1, TVA and LA in the omental fat increased compared to non-supplemented goats (Gagaoua et al, 2023). The increase in C18:1 in muscle or adipose tissues in response to higher grain levels in the diet could be due to the increase in the D9 desaturase enzyme activities necessary for the conversion of C18:0 to C18:1, which can also be seen in sheep and cattle.…”
Section: Influence Of Diets On Health Enhancing Fatty Acids In Chevonmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that feeding goats with a grain diet containing threefold C18:1 compared to an alfalfa hay diet increased C18:1 in both IMF (i.e., marbling) and subcutaneous fat. Thus, when East African goats were supplemented with a grain diet (27% sunflower seed cake + 70% maize bran), the proportions of C18:1, TVA and LA in the omental fat increased compared to non-supplemented goats (Gagaoua et al, 2023). The increase in C18:1 in muscle or adipose tissues in response to higher grain levels in the diet could be due to the increase in the D9 desaturase enzyme activities necessary for the conversion of C18:0 to C18:1, which can also be seen in sheep and cattle.…”
Section: Influence Of Diets On Health Enhancing Fatty Acids In Chevonmentioning
confidence: 98%
“…Various factors affect the FA composition of goat meat, particularly the diet of the animal. Meat from goats grazing rangeland forages (Liotta et al, 2020) or high-forage diets supplemented with n-3 PUFA sources contain increased contents of n-3 PUFA and the BHIs than those raised intensively on high grain diets (Gagaoua et al, 2023). It has been reported that feeding goats with a grain diet containing threefold C18:1 compared to an alfalfa hay diet increased C18:1 in both IMF (i.e., marbling) and subcutaneous fat.…”
Section: Influence Of Diets On Health Enhancing Fatty Acids In Chevonmentioning
confidence: 99%